Behavior of high-performance concrete beams having tension lap spliced anchor-ended bars under repeated loading. (1st January 2023) - Fawzy, Tarek; Khalil, Abdel-Hakim; Atta, Ahmed; Afefy, Hamdy M.; Ellithy, Mohamed
Highlights: New lap splicing technique for tensile steel bars has been developed. The developed technique was based on anchor-ended bars using steel end plats. Experimental tests confirm the adequacy of the adopted technique under the effect of repeated loading. Based on the findings of the numerical simulation, a proposed equation was obtained to predict the ultimate splice strength of the anchor-ended bars. Abstract: In the current paper, a newly developed technique in tension lap splices of steel bars is presented and investigated to verify its efficiency. Consequently, an experimental and numerical study on sixteen high-performance concrete (HPC) specimens containing lap splices without confining reinforcement were performed. The experimental program comprised two phases; the first one was a preliminary study that involved concrete prisms containing the developed splices and tested under axial tension, while the second phase was four-point flexural testing of RC beams having the adopted tension splices and subjected to repeated loading. Both phases included two sub-groups; a reference sub-group having conventional straight-ended splices and the other sub-group implicated in the newly developed technique based on anchor-ended splices. Experimental tests showed that by applying the developed technique, not only higher tensile stress at failure was achieved but also a bond-induced failure was switched to a flexural failure. Furthermore, a splice length of five times bar diameter was found to be sufficient to achieve the full tensile strength of the reinforcing steel bars in the case of the anchor-ended technique. Finally, numerical modeling was employed to study further parameters about the anchor-ended splices. As a result, a proposed equation was obtained based on statistical analysis to predict the ultimate strength of the anchor-ended splice.